Assessing protected areas as climate refugia for threatened plant species in Britain - Freya R. Read; Rachel J. Warmington; Colin M. Beale (PLoS ONE, 2026)
Climate change is causing the loss or movement of suitable habitats, forcing species to undergo range shifts. However, many may be unable to move to suitable locations, resulting in increased extinctions. Climate refugia, areas maintaining suitable conditions for species now and in the future, offer protection from climate change. These refugia are categorised as in situ, where species are currently present, and ex situ, where they are not. We aimed to identify climate refugia for rare vascular plant species in Britain and examined whether refugia with the highest number of suitable species share any common features. Using predicted 2080 distributions, we identified protected areas in Britain that act as in situ or ex situ refugia for 12 of Plantlife’s focal plant species. This study revealed that many current habitats will become unsuitable by 2080, highlighting the urgent need to protect refugia. The limited availability of in situ refugia underscores the importance of ex situ refugia as potential habitats. Our findings indicated that protected areas with higher elevations, larger elevational ranges, higher latitude and longitude and larger area will provide climate refugia for a greater number of species. This information can be used to guide the selection and management of protected areas and identify receptor sites for species introductions.